The Ambiguity of Norms in Article 66 (C) of Law No. 30/1999 on Arbitration And Alternative Dispute Resolution: Causes, Implications And Resolutions - Muhamad Dzadit Taqwa; Tazkia Nafs Azzahra; Maria Jasmine Putri Subiyanto (Jurnal Dinamika Hukum, 2022)
According to Article 66 Letter C of Law Number 30/1999, one of the requirements for an international arbitral award to be accepted and executed in Indonesia is that it does not violate public order.  There is an issue with the norms’ ambiguity; it concerns the definition and the application of the term "public order". As a result, international arbitration awards are more likely to be overturned based on quo conditions. This paper explores the causes and the implications of this ambiguous term. Following then, various potential resolutions to the problem were provided. but removing the article might not be a wise option. Although various publications have studied the recognition and execution of foreign arbitral awards, no comprehensive examination of Article 66 Letter C of Law Number 30/1999 could be identified.Keywords: international arbitral awards, norms’ ambiguity, public order, recognition.